2003
DOI: 10.1021/es025985u
|View full text |Cite
|
Sign up to set email alerts
|

Bioreactive Barriers:  A Comparison of Bioaugmentation and Biostimulation for Chlorinated Solvent Remediation

Abstract: A side-by-side comparison of bioaugmentation, biostimulation, and a recirculation-only control was implemented in a chloroethene-contaminated aquifer. The objective was to develop a contaminant mass balance based on the analysis of groundwater and aquifer solids and to quantify key dechlorinating populations during treatment to determine their relation to the rate of chloroethenes removed. The bioaugmentation strategy, using a Dehalococcoides-containing PCE-to-ethene dechlorinating inoculum enriched from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
221
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(229 citation statements)
references
References 23 publications
7
221
1
Order By: Relevance
“…Several microbial groups carry out respiratory reductive dechlorination 1 , but one genus, Dehalococcoides, seems particularly adapted to a unique niche, and the bacteria are only known to use chloroorganics as electron acceptors and hydrogen as an electron donor for growth. Several studies have now shown successful application of Dehalococcoides-containing cultures for in situ remediation of contaminated sites 2,3 . The recently described genome sequence of D. ethenogenes, strain 195 (ref.…”
mentioning
confidence: 99%
“…Several microbial groups carry out respiratory reductive dechlorination 1 , but one genus, Dehalococcoides, seems particularly adapted to a unique niche, and the bacteria are only known to use chloroorganics as electron acceptors and hydrogen as an electron donor for growth. Several studies have now shown successful application of Dehalococcoides-containing cultures for in situ remediation of contaminated sites 2,3 . The recently described genome sequence of D. ethenogenes, strain 195 (ref.…”
mentioning
confidence: 99%
“…Amplification efficiency, standard curve slope, r 2 value, y-intercept, C T determination method, are more rarely reported, however, a recent study provided a summary of many of these parameters . Detection limits are more frequently reported, some examples for soil, sediment or liquid samples are as follows: 10 2 copies per g of aquifer material (Lendvay et al, 2003); 120 copies per g of soil (Sleep et al, 2006); ∼ 10 3 copies per L of groundwater (Rahm et al, 2006b); 100 to 1000 copies per L of groundwater ; and 500 copies per L bench-scale aquifer effluent (Sleep et al, 2006).…”
Section: Pcr Parameters Of Current Methodsmentioning
confidence: 99%
“…to in situ bioremediation (Adamson et al, 2003;Ellis et al, 2000;Hendrickson et al, 2002;Lendvay et al, 2003;Lu et al, 2006;Major et al, 2002;Nijenhuis et al, 2007;Rahm et al, 2006b). Initial investigations involved the addition of mixed cultures containing Dehalococcoides spp.…”
Section: Contribution To Bioremediation Effortsmentioning
confidence: 99%
See 2 more Smart Citations